Fatigue Deformation and Energy Change of Single-Joint Sandstone After Freeze-Thaw Cycles and Cyclic Loadings - Shen, Yanjun; Yang, Hongwei; Jin, Long; Zhang, Huan; Yang, Gengshe; Zhang, Jinyuan (Frontiers in Earth Science, 2019)
In cold regions, saturated fractured rock is prone to crack initiation, extension, and branching along the original fracture end under the effect of freeze-thaw (F-T) cycles and cyclic fatigue loadings. The resulting strength deterioration is accompanied by large amounts of pore growth, which results in localized damage and fracturing along the crack end and even causes overall failure. To study the fatigue damage behaviors of fractured rocks under F-T cycles and cyclic loadings, single-joint quasi-sandstone specimens with joint angles of 45° and 90° were prepared. Subsequently, F-T damage tests with 0, 10, and 20 cycles and cyclic loading tests with different stress levels were performed. The F-T damage features are discussed based on the binarization image of localized damage along the joint ends and their wave velocity variations. It is found that the frost damage of single-joint quasi-sandstone tends toward a strip with localized fatigue characteristics. Moreover, the changes of strain compliance and dissipated energy are studied under the effect of loading-unloading fatigue. Some of the interesting phenomena observed are as follows: (i) during the early stage of cyclic loading, the joint can be compacted; nevertheless, it tends to expand along the fracture direction once it passes the elastic stage, and the irreversible plastic deformation is stable at this stage. (ii) The cracks caused by F-T damage in the 45° single-joint samples deflect along the fracture direction, in contrast to the 90° single-joint specimens. Moreover, the samples with a 45° single joint are more susceptible to original fracture at the early stage of the failure process, which results in a different failure mode from that of the 90° single-joint samples. (iii) The F-T cycles and cyclic loadings have a coupling effect on the single-joint sandstone. The strain compliance and hysteresis energy keep increasing uniformly after the F-T cycles and cyclic loadings.